Polyvinyl alcohol composite film of molybdenum diselenide coated WO3 nanosheet containing 1T-MoSe2 as well as preparation method and application of polyvinyl alcohol composite film

Through the polyvinyl alcohol composite film coated with WO3 nanosheets with 1T-MoSe2, the problem of polarization relaxation loss and limited absorption performance in terahertz wave absorbing materials is solved, and the efficient absorption performance of the wideband is achieved, which is suitable for terahertz. Shielding and stealth coating of waves.

CN119144106AActive Publication Date: 2024-12-17NANJING UNIV

Patent Information

Application Number
CN202411066379.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-17
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

Existing terahertz wave absorbing materials have difficulty providing efficient polarization relaxation loss and wave absorption performance, and the metamaterial design is complex and costly, making it difficult to achieve broadband absorption performance.

Method used

Polyvinyl alcohol composite film coated with WO3 nanosheets using 1T-MoSe2 molybdenum diselenide, 1T-MoSe2 nanosheets were prepared by hydrothermal method, and combined with WO3 nanosheets to form a composite material with a unique heterostructure. , use polyvinyl alcohol as a matrix to prepare ultra-thin polymer films.

Benefits of technology

Effective shielding performance is achieved in the range of 0.2-1.8 THz, with an average terahertz shielding performance reaching 43dB, which is mainly achieved through an absorption mechanism. The reflective shielding performance accounts for a small proportion. The material is lightweight, ultra-thin and has strong absorption performance. It is suitable for micro Electronics and stealth coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144106A_ABST
    Figure CN119144106A_ABST
Patent Text Reader

Abstract

The invention relates to a polyvinyl alcohol composite film of molybdenum diselenide coated WO3 nanosheet containing 1T-MoSe2, a preparation method and application, the molybdenum diselenide nanosheet containing 1T-MoSe2 synthesized by a hydrothermal method is combined with the (100) surface of the WO3 nanosheet to construct a composite material of a heterostructure, the composite material is dispersed in a 10wt% polyvinyl alcohol solution, pouring is performed to obtain a polymer film, and the polymer film is coated with the molybdenum diselenide coated WO3 nanosheet containing 1T-MoSe2. When the thickness of a composite film sample is 500m, the material with the optimal proportion shows effective shielding effectiveness (the shielding effectiveness is greater than or equal to 10dB) within the whole test range of 0.2-1.8 THz, the shielding effectiveness at 1.62 THz can reach 71.48 dB, and the average terahertz shielding effectiveness reaches 43.03 dB. The material has the advantages of light weight, ultra-thinness, strong absorption and the like, and has important value in the fields of terahertz signal shielding of microelectronic devices, stealth coatings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of terahertz wave absorption, and specifically relates to a composite material in which metal phase molybdenum diselenide is grown on tungsten trioxide nanosheets as a filler, a polymer film with polyvinyl alcohol as a substrate, and its application in terahertz wave absorption. Background Art

[0002] The frequency of terahertz waves is located in a "vacuum zone" between infrared and microwaves. Due to its comprehensive advantages such as high bandwidth, high penetration, low energy, coherence, and fingerprint spectroscopy, it has important application value in many important fields such as life science, material science, astronomy, atmosphere and environmental monitoring, communications, and national security. However, with the rapid development of high-frequency radio technology and the widespread application of electronic equipment, which has brought great convenience to human life, the derived electromagnetic pollution problem seriously threatens human health and also damages the stability of precision electrical equipment. In addition, in the military field, due to the development of radar detection technology, the new generation of high-speed aircraft faces severe threats of radar-guided attacks, which seriously affects the efficient penetration and survivability of future battlefields. Therefore, the rapidly developing terahertz technology requires high-performance terahertz absorbers to suppress electromagnetic interference and achieve terahertz stealth. Terahertz wave absorbing materials can dissipate terahertz waves in the form of heat inside the material through various attenuation mechanisms. These materials need to meet the properties of low density, ultra-thinness, and strong absorption to match the micro-quantity and ultra-thin coating technology of military and electronic products.

[0003] Metallic phase molybdenum diselenide (1T-MoSe2) flakes are similar to graphene sheets. Compared with semiconductor phase molybdenum diselenide (2H-MoSe2), they have better intrinsic activity and conductivity. Their diameter is about 50nm, while the wavelength of terahertz waves is far different. The large size difference makes it impossible to achieve electromagnetic wave loss and attenuation through resonant absorption. WO3 has a unique octahedral crystal structure, which is prone to lattice distortion under small external stimuli. This deformation can cause changes in the crystal structure and local electrons of WO3, thereby improving its electrochemical properties and conductivity. In addition, its rich oxygen vacancies can modulate its dielectric loss capacity, making it have excellent prospects in electromagnetic wave absorption. Polyvinyl alcohol (PVA) is a polymer material with good optical properties and solubility, good flexibility, stretchability and film-forming properties, and is an excellent choice for preparing polymer films.

[0004] Terahertz waves are composed of rapidly changing electric and magnetic fields. The key factor that determines the terahertz wave dissipation performance of the absorbing material is the dielectric loss or magnetic loss capacity of the material itself. In the terahertz band, the magnetic loss capacity is low, and the dielectric loss phenomenon is more prominent. The diversity and complexity of the loss process provide opportunities for seeking strong absorption. The electromagnetic parameters of the absorber of a single component material are difficult to control due to its single absorption mechanism and low conductivity, resulting in the inability to obtain excellent terahertz absorption capacity. In order to meet the needs of ideal terahertz wave absorption, strategies such as constructing a conductive network, optimizing components, and constructing a heterogeneous interface are usually adopted to achieve the adjustment of electromagnetic parameters, controllable impedance matching, and significant synergistic effects between different components.

[0005] In recent years, the research on terahertz artificial metamaterials has developed rapidly. The essence of metamaterials is that several narrow-band absorption materials and metal materials absorb electromagnetic waves through different design structures and assembly methods. Although the ability to controllably absorb electromagnetic waves of a specific frequency can be achieved, it is difficult for most metamaterials to achieve broadband absorption performance, and they have problems such as complex design and high device preparation costs. On the other hand, there is research on the intrinsic electromagnetic wave absorption of materials, such as Mxene, carbon nanotubes or graphene. These materials have very good conductivity, which enables them to have excellent conductive losses in a wide band, but these materials will cause strong surface reflections due to impedance matching mismatch and other reasons, which greatly reduces the terahertz absorption performance. And with the development of microelectronic devices, the requirements for shielding materials are becoming increasingly stringent, and the demand for ultra-thin, lightweight, and highly absorbing thin film materials is also imminent. Therefore, the application prospects of preparing ultra-thin, high-absorption and low-reflection terahertz shielding thin film materials are very broad. Summary of the invention

[0006] The purpose of the present invention is to provide a polyvinyl alcohol composite film of molybdenum diselenide coated WO3 nanosheets containing 1T-MoSe2, a preparation method and its application in terahertz wave absorption, so as to solve the problem that existing terahertz wave absorption materials are difficult to provide efficient polarization relaxation loss and have limited wave absorption performance.

[0007] The technical solution for achieving the purpose of the present invention is:

[0008] In the first aspect, a polyvinyl alcohol composite film of WO3 nanosheets coated with molybdenum diselenide containing 1T-MoSe2 is provided, wherein the composite film is filled with a composite material having a unique heterogeneous structure formed by molybdenum diselenide containing 1T-MoSe2 attached to WO3 nanosheets, and polyvinyl alcohol (PVA) is used as a matrix, wherein 1T-MoSe2 is combined with the WO3 (001) crystal plane.

[0009] Preferably, the molybdenum diselenide containing 1T-MoSe2 is a nanosheet structure with a diameter of 30-50 nm.

[0010] Preferably, the WO3 nanosheets are thin-layer nanosheets with a plane diameter of 1-3 μm.

[0011] Preferably, molybdenum diselenide containing 1T-MoSe2 is attached to WO3 nanosheets to form a composite material with a unique heterogeneous structure, wherein the mass fraction of 1T-MoSe2 in the composite material is 30-50%, preferably 40%, and the mass fraction of WO3 is 20%.

[0012] In a second aspect, the present invention provides a method for preparing a polyvinyl alcohol composite film of molybdenum diselenide coated WO3 nanosheets containing 1T-MoSe2 as described in the first aspect, the steps being as follows:

[0013] Step 1: Dissolve sodium molybdate dihydrate and selenium powder in deionized water and stir mechanically for 1 hour, and perform ultrasound until the solution is uniformly dispersed, which is recorded as solution A;

[0014] Step 2: Sodium borohydride in a molar ratio of 2 to 4 with respect to sodium molybdate dihydrate is added to solution A, and after being stirred evenly, the solution is transferred to a high-pressure reactor, reacted at 200° C. for 16 hours, and then vacuum dried after cleaning to obtain molybdenum diselenide nanosheets containing 1T-MoSe2;

[0015] Step 3: dissolve sodium tungstate dihydrate and sodium chloride in deionized water, adjust the pH value of the solution, add the molybdenum diselenide nanosheets containing 1T-MoSe2 described in step 2, stir evenly and transfer to a high-pressure reactor, and react at 180°C for 24 hours;

[0016] Step 4: After the reaction is completed, washing and vacuum drying are performed to obtain a composite material of WO3 nanosheets coated with molybdenum diselenide containing 1T-MoSe2;

[0017] Step 5: Place the composite material of step 4 in a polyvinyl alcohol (PVA) solution, stir evenly, and then drop-coat the resulting mixed solution on a smooth silicon wafer, and dry at 35° C. under a vacuum environment to form a film.

[0018] Preferably, in step 3, HCl is added dropwise to adjust the pH value of the solution to 2.

[0019] Preferably, in step 5, the concentration of the PVA solution is 10 wt %, which has better film-forming properties.

[0020] Preferably, in step 5, the composite material of step 4 accounts for 20% of the total mass of the mixed solution.

[0021] In a third aspect, the present invention provides an application of a polyvinyl alcohol composite film of molybdenum diselenide-coated WO3 nanosheets containing 1T-MoSe2 described in the first aspect in terahertz wave absorption.

[0022] Preferably, the composite film has effective shielding effectiveness (shielding effectiveness ≥ 10 dB) within 0.2-1.8 THz.

[0023] Preferably, the average terahertz shielding effectiveness of the composite film within 0.2-1.8 THz is not less than 43 dB.

[0024] In a fourth aspect, the present invention provides a terahertz absorption material, which is formed by the polyvinyl alcohol composite film of molybdenum diselenide-coated WO3 nanosheets containing 1T-MoSe2 as described in the first aspect.

[0025] In a fifth aspect, the present invention provides a terahertz absorber, which comprises the polyvinyl alcohol composite film of WO3 nanosheets coated with molybdenum diselenide containing 1T-MoSe2 as described in the first aspect.

[0026] In a sixth aspect, the present invention further provides a stealth coating, which is formed by coating a polyvinyl alcohol composite film of molybdenum diselenide-coated WO3 nanosheets containing 1T-MoSe2 as described in the first aspect on a substrate.

[0027] Compared with the prior art, the invention has the following beneficial effects: the invention relates to a polymer film containing a 1T-MoSe2 molybdenum diselenide-coated tungsten trioxide nanosheet composite material as a filler and polyvinyl alcohol as a matrix, and its application in terahertz shielding. The advantage of 1T-MoSe2 nanosheets over 2H-MoSe2 nanosheets is that they have stronger conductivity. The transition from 2H phase to 1T phase can significantly improve the electron transfer ability of MoSe2. Since the Fermi level of 1T-MoSe2 matches the energy level of tungsten trioxide, under the radiation of periodic terahertz waves, the electrons of 1T-MoSe2 will be injected and released into the tungsten trioxide nanosheets. This tiny external stimulus will change the electron cloud around the W atom, and the injection / release of electrons causes the electron cloud to move between W(VI) and W(VI). -) to enhance the dielectric loss capacity of the material, thereby improving the form of polarization relaxation to promote terahertz wave absorption. The results show that when the thickness of the composite film sample is 500μm, the material with the best ratio exhibits effective shielding effectiveness (shielding effectiveness ≥ 10dB) in the entire test range of 0.2-1.8THz, and the shielding effectiveness can reach 71.48dB at 1.62THz, and the average terahertz shielding effectiveness reaches 43.03dB. And most of the shielding effectiveness comes from the absorption of the material, and the reflected shielding effectiveness accounts for a very small proportion of the total shielding effectiveness. This material has the advantages of light weight, ultra-thinness and strong absorption, and is of great value in the fields of terahertz signal shielding of microelectronic devices and stealth coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 (a) and (b) are scanning electron microscope images of semiconductor phase 2H-MoSe2 (MoSe2-O) nanosheets; (c) is the X-ray diffraction pattern of semiconductor phase 2H-MoSe2 (MoSe2-0) nanosheets; (d) is the total shielding effectiveness diagram of semiconductor phase MoSe2-0 / PVA film in the range of 0.2-1.8THz.

[0029] Figure 2 Schematic diagram of the energy levels of metallic phases 1T-MoSe2 and WO3 obtained through first-principles calculations.

[0030] Figure 3 (a) is the scanning electron microscope image of WO3 nanosheets; (b) is the scanning electron microscope image of MoSe2-2 / WO3 composite material; (c) is the scanning electron microscope image of local MoSe2-2 / WO3 composite material; (d) is the X-ray diffraction pattern of MoSe2-2 and MoSe2-2 / WO3 composite materials.

[0031] Figure 4 (a) is the total shielding effectiveness diagram of the (MoSe2-2 / WO3) / PVA composite film with an optimal ratio of 500 μm in thickness in the range of 0.2-1.8 THz; (b) is the absorption shielding effectiveness diagram of the (MoSe2-2 / WO3) / PVA composite film with an optimal ratio in the range of 0.2-1.8 THz.

[0032] Figure 5 (a) is the absorptivity of the (MoSe2-2 / WO3) / PVA composite film with the optimal ratio and thickness of 500 μm in the range of 0.2-1.8 THz; (b) is the reflectivity of the (MoSe2-2 / WO3) / PVA composite film with the optimal ratio and thickness of 500 μm in the range of 0.2-1.8 THz.

[0033] Figure 6(a) is the total shielding effectiveness diagram of four composite films of (MoSe2-0 / WO3) / PVA, (MoSe2-1 / WO3) / PVA, (MoSe2-2 / WO3) / PVA and (MoSe2-3 / WO3) / PVA in the range of 0.2-1.8 THz, and (b) is the average shielding effectiveness diagram of composite films with different contents of metal phase in the range of 0.2-1.8 THz. DETAILED DESCRIPTION

[0034] The present application is further described below in conjunction with specific embodiments.

[0035] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0037] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0038] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0039] As used herein, the term "at least one of..." is intended to be synonymous with "one or more of...". For example, "at least one of A, B, and C" explicitly includes only A, only B, only C, and their respective combinations. Concentrations, amounts, and other numerical data may be presented in a range format herein. It should be understood that such a range format is used only for convenience and brevity, and should be flexibly interpreted as including not only the numerical values ​​explicitly stated as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, just as each numerical value and sub-range is explicitly stated. For example, a numerical range of about 1 to about 4.5 should be interpreted as including not only the explicitly stated limit values ​​of 1 to about 4.5, but also individual numbers (such as 2, 3, 4) and sub-ranges (such as 1 to 3, 2 to 4, etc.). The same principle applies to ranges that state only one numerical value, such as "less than about 4.5", which should be interpreted as including all of the above values ​​and ranges. In addition, this interpretation should apply regardless of the breadth of the described range or feature.

[0040] The molybdenum diselenide containing 1T-MoSe2 of the present invention is prepared by a hydrothermal method, and the content of 1T-MoSe2 in the molybdenum diselenide is changed by controlling the amount of sodium borohydride, a reducing agent, during the reaction process. The present invention constructs a unique heterostructure composite by combining the (001) face of tungsten trioxide with 1T-MoSe2, and prepares an ultra-thin polymer film using molybdenum diselenide containing 1T-MoSe2 coated tungsten trioxide nanosheets as fillers and polyvinyl alcohol (PVA) as a matrix. Due to the matching of the Fermi level of 1T-MoSe2 and the energy level of the conduction band of tungsten trioxide, the periodic injection and release of electrons on the 1T-MoSe2 nanosheets to the tungsten trioxide nanosheets are promoted under the radiation of a periodically changing terahertz field. WO3 has a unique octahedral crystal structure and is prone to lattice distortion under relatively small external stimuli. This deformation can cause changes in the crystal structure and local electrons of WO3, thereby achieving W(VI) and W(VI) -) is reversed, and the polarization relaxation induced by the atomic valence reversal significantly enhances the terahertz wave absorption performance. The present invention prepares high-performance broadband absorption materials based on the physical properties of the material itself. The tungsten trioxide nanosheets coated with metal phase molybdenum diselenide prepared by the present invention show excellent terahertz wave absorption performance in the range of 0.2-1.8THz due to the change of its inherent dipole moment. The base of the terahertz wave absorption film in the range of 0.2-1.8THz is 10wt% PVA solution, and the filling ratio of the MoSe2 / WO3 composite nanomaterial containing the metal phase MoSe2 is 20wt%. The terahertz wave absorption performance and reflection performance in the range of 0.2-1.8THz are obtained from the transmission mode and reflection mode of the terahertz time-domain spectrum. The electrical and magnetic properties of the material itself can be obtained through the terahertz time-domain spectrum system, and the refractive index, extinction coefficient and absorption coefficient of the material can be obtained through the terahertz time-domain spectrum.

[0041] In the previous work, the present invention compared the influence of the proportion of WO3 in 2H-MoSe2 and WO3 composite materials on the terahertz absorption performance, prepared MoSe2 / WO3 composite materials, in which the mass proportions of WO3 were 10%, 20%, 30% and 40%, respectively, and tested the performance of the composite materials through terahertz time domain spectrum. It was found that the absorption performance of MoSe2 / WO3 composite materials was the best when the mass proportion of WO3 was 20%. Therefore, the mass proportion of tungsten trioxide in the molybdenum diselenide-coated tungsten trioxide nanosheet composite material containing metal phase MoSe2 involved in the present invention is fixed to 20%, and only the influence of the polymer film constructed by the molybdenum diselenide-coated tungsten trioxide nanosheet composite material with different proportions of metal phase MoSe2 on the terahertz absorption performance is considered.

[0042] The raw materials and instruments used in the examples are not specifically limited to their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] 0.242g of sodium molybdate dihydrate and 0.158g of selenium powder were added to 40ml of deionized water together with different amounts of sodium borohydride (0.076g, 0.152g, 0.228g, 0.304g), ultrasonicated for 30 minutes, and then vigorously magnetically stirred for 50 minutes. When the molar mass ratio of sodium borohydride to sodium molybdate dihydrate was 1:1, that is, the amount of sodium borohydride added was 0.076g, the pure semiconductor phase 2H-MoSe2 (standard) was obtained by hydrothermal reaction. Marked as MoSe2-0); when the molar ratio of sodium borohydride to sodium molybdate dihydrate is 2:1, that is, the amount of sodium borohydride added is 0.152g, it is marked as MoSe2-1; when the molar ratio of sodium borohydride to sodium molybdate dihydrate is 3:1, that is, the amount of sodium borohydride added is 0.228g, it is marked as MoSe2-2; when the molar mass ratio of sodium borohydride to sodium molybdate dihydrate is 4:1, that is, the amount of sodium borohydride added is 0.304g, it is marked as MoSe2-3. The solution was then transferred to a Teflon-lined stainless steel autoclave. The autoclave was heated from room temperature (RT) to 200°C at a rate of 20-25°C / min in a conventional oven and maintained at the target temperature for 16 hours. After the reaction was completed, the oven was turned off and cooled naturally to room temperature. The product formed was then collected by centrifugation at 3000-6000rpm and washed three times with deionized water and ethanol. Finally, the product was dried at 70 °C in vacuum.

[0045] The 2H-MoSe2, i.e., MoSe2-0, obtained in this example was tested using a scanning electron microscope and X-ray diffraction.

[0046] The scanning electron microscopy results are as follows Figure 1 As shown in (a) and (b) in the figure, the nanosheet structure of MoSe2-0 is generated by hydrothermal method. The molar ratio of sodium borohydride to sodium molybdate dihydrate is 1:1 during the reaction, and the diameter of the nanosheet is about 50nm. Figure 1 As shown in (c), its peak position corresponds to the peak position of the standard card PDF#29-0914, proving that no other impurities are generated. Figure 3 As shown in (d), the characteristic peaks at 12.7°, 31.7°, 38.3° and 56.2° correspond to the (002), (100), (103) and (110) planes, respectively.

[0047] Example 2

[0048] 0.4125g of sodium tungstate dihydrate powder and 0.145g of sodium chloride powder were dissolved in 40ml of deionized water, a small amount of hydrochloric acid was added to adjust the pH value of the solution, the solution environment was adjusted to pH = 2, 1.16g of MoSe2-0 prepared in Example 1 and MoSe2-1, MoSe2-2 and MoSe2-3 were added respectively, and after ultrasonication for 30 minutes, magnetic stirring was performed for 1h to make the precursor material evenly dispersed in the solution, and then transferred to a 50mL high-pressure reactor and reacted at 200℃ for 24h. The product was vacuum dried at 70℃ to obtain MoSe2-0 / WO3, MoSe2-1 / WO3, MoSe2-2 / WO3 and MoSe2-3 / WO3 composite materials with 1T-MoSe2 proportions of 0%, 30%, 40% and 50%, respectively.

[0049] Figure 2 The present invention is a band structure diagram of a heterostructured composite constructed by coating a molybdenum diselenide nanosheet containing 1T-MoSe2 on a WO3 nanosheet. The work function of 1T-MoSe2 obtained by first-principles calculation is 4.34 eV, while the work function of the WO3 (001) surface is 5.04 eV, and the bandwidth is 2.89 eV. After the 1T-MoSe2 nanosheet and the WO3 nanosheet form a heterojunction surface, the Fermi level is unified, and the injection and release of electrons from the metal phase molybdenum diselenide nanosheet to the tungsten trioxide (001) surface are realized in a periodic electromagnetic field. This electron transfer can cause changes in the crystal structure and local electrons of WO3, change the electron cloud distribution around the W atom, and make W(VI) and W(VI) - ) repeatedly changes between the two, improving the dielectric loss performance of the material and thus enhancing the terahertz absorption performance.

[0050] The MoSe2-2 / WO3 composite material prepared in this example was analyzed by scanning electron microscopy (SEM) X-ray diffraction, and pure WO3 nanosheets (prepared by hydrothermal method) were also analyzed by SEM for comparison.

[0051] The electron microscope image of pure WO3 nanosheets is shown in Figure 3 As shown in (a), the hydrothermal generation of thin flakes with a diameter of about 1-3 μm, the electron microscope image of the MoSe2-2 / WO3 composite material is as follows Figure 3 As shown in (b) and (c), the larger tungsten trioxide nanosheets are coated by the smaller molybdenum diselenide nanosheets containing 1T-MoSe2, that is, the molybdenum diselenide nanosheets grow well on the large tungsten trioxide; the X-ray diffraction test of MoSe2-2 / WO3 composite material is shown in Figure 3 As shown in (d), compared with MoSe2-2 nanosheets, the main peak positions are the same, only the crystallinity is different. The crystallinity of tungsten trioxide is good, which is in good agreement with the standard card PDF#33-1387. In addition, it does not contain any impurities.

[0052] Add 1.1g of polyvinyl alcohol powder to 10ml of deionized water, and stir the solution mechanically at 90℃ for 1 hour to gradually turn the solution into a viscous liquid. Add 2.78g of the MoSe2-0 / WO3, MoSe2-1 / WO3, MoSe2-2 / WO3 and MoSe2-3 / WO3 composite materials prepared above, respectively, and continue stirring for 30 minutes to make the composite materials uniformly dispersed in the 10% PVA solution. Take a small amount of solution and cast it on a smooth silicon wafer. Dry it at 35℃ for 12h under vacuum conditions to finally obtain four (MoSe2-0 / WO3) / PVA, (MoSe2-1 / WO3) / PVA, (MoSe2-2 / WO3) / PVA and (MoSe2-3 / WO3) / PVA polymer films with a film thickness of 500μm.

[0053] The terahertz wave absorption performance of four polymer films in the range of 0.2-1.8 THz was tested using a terahertz time-domain spectroscopy system. The total shielding effectiveness, absorption shielding effectiveness, absorptivity and reflectivity of the composite film were obtained through the transmission mode and reflection mode of the terahertz time-domain spectroscopy system.

[0054] Among them, the total shielding effectiveness of (MoSe2-2 / WO3) / PVA polymer film material in the range of 0.2-1.8THz and Figure 4 As shown in (a): When the film thickness is 500μm, the film exhibits effective shielding effectiveness (shielding effectiveness ≥ 10dB) in the entire test range of 0.2-1.8THz, and the shielding effectiveness can reach 71.48dB at 1.65THz. Figure 4 (b) in the figure describes the absorption shielding effectiveness of the film. At 1.65 THz, the absorption shielding effectiveness can reach 71.4 dB, which is almost the same as the total shielding effectiveness, and the effective shielding band occupies the entire test, proving that the shielding effectiveness of the film is dominated by absorption. Figure 5 (a) in the figure describes the absorption rate diagram of the film. In the range of 0.2-1.8 THz, the absorption rate is mostly around 99%. At 1.72 THz, the absorption rate is as low as 93%. This is because the polymer PVA has a certain reflection phenomenon at 1.72. Figure 5 (b) in the figure describes the reflectivity of the film, which has a maximum reflectivity of no more than 6.7% and is basically 0 at most frequencies. This also proves that the shielding effectiveness of the film against terahertz waves mainly comes from the absorption of the material, and the reflection is negligible.

[0055] Figure 6(a) is the total shielding effectiveness of polyvinyl alcohol composite films containing different proportions of 1T-MoSe2 and molybdenum diselenide coated WO3 nanosheets in the range of 0.2-1.8THz, among which the shielding effectiveness of (MoSe2-3 / WO3) / PVA film can reach 55.3dB at 1.55THz, the shielding effectiveness of (MoSe2-2 / WO3) / PVA film can reach 71.48dB at 1,65THz, and the shielding effectiveness of (MoSe2-1 / WO3) / PVA film can reach 46.3dB at 1.27THz, and the effective shielding effectiveness (≥10dB) of these films can reach 100% in the test band. However, the shielding effectiveness of (MoSe2-0 / WO3) / PVA film without metal phase can only reach 44dB at 1.67THz. In addition, WO3 as an electron acceptor also plays an important role in absorption. When WO3 and 1T-MoSe2 are absent, the performance of MoSe2-0 / PVA polymer film is as follows: Figure 1 As shown in (d), the effective shielding effectiveness range in the 0.2-1.8THz band can only reach 88% (effective shielding effectiveness ≥ 10dB), and the highest shielding effectiveness at 1.67THz can only reach 36.5dB, proving that its performance is significantly reduced when WO3 and 1T-MoSe2 are not present.

[0056] Figure 6 (b) in the figure is the average shielding effectiveness of each of the four films. The average shielding effectiveness of the (MoSe2-0 / WO3) / PVA film without 1T-MoSe2 is only 24.37 dB, which is much lower than the composite film of molybdenum diselenide coated with tungsten trioxide containing 1T-MoSe2. In particular, the average shielding effectiveness of the (MoSe2-2 / WO3) / PVA film in the test band can reach 43.04 dB, which has excellent terahertz shielding performance dominated by absorption.

[0057] Therefore, under the irradiation of terahertz waves, the molybdenum diselenide-coated tungsten trioxide nanosheet composite material containing 1T-MoSe2 wrapped in the above polymer film causes the upper electrons of 1T-MoSe2 to be periodically injected and released into the (001) surface of the tungsten trioxide nanosheet, and lattice distortion is very likely to occur under a small stimulus. Since the polarization frequency induced by the atomic valence inversion cannot follow the changes of the high-frequency terahertz wave, this polarization relaxation phenomenon will greatly enhance the absorption and shielding of terahertz waves.

[0058] The above-mentioned implementation cases are only preferred implementation cases in the present invention, but the implementation methods of the present invention are not limited to the above-mentioned implementation cases, such as the various forms of combinations of the schemes in Examples 1 to 4, and any other changes, modifications, substitutions, and combinations made without departing from the spirit and principles of the present invention should be equivalent replacement methods and are within the protection scope of the present invention.

Claims

1. A polyvinyl alcohol composite film containing 1T-MoSe2 molybdenum diselenide coated WO3 nanosheets, characterized in that: The composite film is filled with molybdenum diselenide containing 1T-MoSe2 attached to WO3 nanosheets to form a composite material with a heterogeneous structure, and polyvinyl alcohol is used as a matrix, wherein 1T-MoSe2 is combined with the WO3 (001) crystal plane.

2. The composite film according to claim 1, characterized in that Molybdenum diselenide containing 1T-MoSe2 is a nanosheet structure with a diameter size of 30-50 nm.

3. The composite film according to claim 1, characterized in that WO3 nanosheets are thin-layer nanosheets with a plane diameter of 1-3 microns.

4. The composite film according to claim 1, characterized in that The mass fraction of 1T-MoSe2 in the composite material is 30-50%, preferably 40%, and the mass fraction of WO3 is 20%.

5. A method for preparing a composite film according to any one of claims 1 to 4, characterized in that: Here are the steps: Step 1: Dissolve sodium molybdate dihydrate and selenium powder in deionized water and stir mechanically for 1 h, and perform ultrasound until the solution is uniformly dispersed, which is recorded as solution A. Step 2: Sodium borohydride with a molar ratio of 2 to 4 to sodium molybdate dihydrate is added to solution A, and after stirring evenly, the solution is transferred to a high-pressure reactor, reacted at 200 °C for 16 h, and then vacuum dried after cleaning to obtain molybdenum diselenide nanosheets containing 1T-MoSe2; Step 3: dissolve sodium tungstate dihydrate and sodium chloride in deionized water, adjust the pH value of the solution, add the molybdenum diselenide nanosheets containing 1T-MoSe2 described in step 2, stir evenly and transfer to a high-pressure reactor, and react at 180°C for 24 h; Step 4: After the reaction is completed, washing and vacuum drying are performed to obtain a composite material of WO3 nanosheets coated with molybdenum diselenide containing 1T-MoSe2; Step 5: Place the composite material of step 4 in a polyvinyl alcohol solution and stir evenly. Then, drop-coat the resulting mixed solution on a smooth silicon wafer and dry it at 35° C. under a vacuum environment to form a film.

6. Use of the composite film according to any one of claims 1 to 4 in terahertz wave absorption.

7. The use according to claim 6, characterized in that The composite film has a shielding effectiveness of ≥10dB within 0.2-1.8 THz.

8. A terahertz absorbing material, characterized in that: It is formed by the composite film as claimed in any one of claims 1 to 4.

9. A terahertz absorber, characterized in that: It comprises the composite film as claimed in any one of claims 1 to 4.

10. A stealth coating, characterized in that: The composite film is formed by coating the composite film as claimed in any one of claims 1 to 4 on a substrate.

Citation Information

Patent Citations

  • Adjustable absorber based on molybdenum diselenide disc patterns

    CN110165420A

  • MoSe2 / ferromagnetic metal terahertz radiation source, preparation method and terahertz wave excitation method

    CN111082287A

  • FAR-INFRARED, THz NANOCRYSTALS, HETEROSTRUCTURED MATERIAL WITH INTRABAND ABSORPTION FEATURE AND USES THEREOF

    US20200318255A1

Cited By

  • Absorbent of tungsten trioxide coated magnetic metal as well as preparation method and application of absorbent

    CN119505862A